Targeting Nominal Income Growth or Inflation? - Henrik Jensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 1999)
Within a simple New Keynesian model emphasizing forward-looking behavior of private agents, I evaluate optimal nominal income growth targeting versus optimal inflation targeting. When the economy under consideration is mainly subject to shocks that do not involve monetary policy trade-offs for society, inflation targeting is preferable. Otherwise, nominal income growth targeting may be superior because it induces inertial interest rate behavior that improves the inflation-output gap trade-off. Somewhat paradoxically, inflation targeting is relatively less favorable the more society cares for inflation, and the more persistent are the effects of inflation-generating shocks.
Keywords: 330